Homology modelling and molecular simulation approach to prediction of B-cell and T-cell epitopes in an OMP25 peptide vaccine against Brucella abortus. Issue 5 (24th March 2023) - Jade, Dhananjay; Gupta, Sonal; Mohan, Surender; Ponnambalam, Sreenivasan; Harrison, Michael; Bhatnagar, Rakesh
ABSTRACT: The live attenuated vaccine composition against brucellosis poses potential risks to recipient animals. Therefore, we have analysed an in-silico approach to design a novel multi-epitope vaccine peptide to elicit a desirable immune response against Brucella abortus infection. This study designed a peptide vaccine based on outer membrane protein from B. abortus . The selected OMP sequence shows 0.7575 antigenic proteins. We predicted the T-cell epitopes of different lengths. Cluster analysis was performed for 180 epitope peptides, showcasing a total of 19 clusters, constituting 14 clusters as Consensus clusters and 5 as Singleton clusters. We select the top three clusters which has 24 peptides showing antigen property. Selected 24-antigen peptides were docked with MHC classes I and II and selected the top eight peptides based on binding energy used for molecular dynamic simulation. Immuno-informatics analysis, Molecular Docking and Molecular simulation indicated that epitope peptide vaccine could work as effective peptides helpful in scheming peptide vaccine against B. abortus infection by developing broad-spectrum peptide vaccine in near future. The use of Omp25 as a vaccine candidate has been supported based on previous experimental studies. Multitope vaccine can be developed which can protect mice against virulent B. abortus challenge.